2003
DOI: 10.3354/cr024047
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of global warming on changes in the East Asian monsoon and the related river discharge in a global time-slice experiment

Abstract: Changes in the East Asian monsoon and the related river discharge under global warming conditions are investigated using 2 time-slice simulations of the IS92a scenario with a T106 atmospheric general circulation model (ECHAM4) for 1971 to 1980 and 2041 to 2050. Daily runoff and drainage calculated by the land-surface scheme are used as input to a hydrological model to diagnose changes in the Yangtze River and Zhujiang River discharges. In the future climate, the simulated annual cycle of precipitation over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
2
9
1
Order By: Relevance
“…3 and 7). The strengthening of the EASM is consistent with analyses of coupled climate model simulations by Hu et al (2000) and Bueh et al (2003), who showed that increased future greenhouse gas concentrations intensify the EASM because of an enhanced land-ocean temperature gradient due to larger warming over land. In our experiments, near-surface summer temperatures over Asia increased under increasing greenhouse gases while the SSTs were fixed to climatological values, so that the land-ocean (surface) temperature gradient was enhanced, resulting in a stronger EASM.…”
Section: Easm's Response To Atmospheric Forcingssupporting
confidence: 72%
“…3 and 7). The strengthening of the EASM is consistent with analyses of coupled climate model simulations by Hu et al (2000) and Bueh et al (2003), who showed that increased future greenhouse gas concentrations intensify the EASM because of an enhanced land-ocean temperature gradient due to larger warming over land. In our experiments, near-surface summer temperatures over Asia increased under increasing greenhouse gases while the SSTs were fixed to climatological values, so that the land-ocean (surface) temperature gradient was enhanced, resulting in a stronger EASM.…”
Section: Easm's Response To Atmospheric Forcingssupporting
confidence: 72%
“…On an annual basis, the simulated runoff decreased by 0.3% in 2010–2040 and 2.5% in 2070–2100 with respect to the baseline period, corresponding to an expected monetary loss of 0.37 and 1.43 million US$ per month, respectively. However, on a seasonal scale the results indicated that climate change will affect the regional water regime by increasing spatial and temporal variability of water resources, as observed also in other regions (Bueh et al , 2003; Graves and Chang, 2007; Bae et al , 2008). In the present period, rainfall distribution in the study area presents a slight seasonality, where the drier periods occur in autumn–winter and wetter periods in spring–summer.…”
Section: Discussionsupporting
confidence: 62%
“…[21] Previous studies based on climate model simulations projected that the Asian monsoons would weaken in winter and strengthen in summer under greenhouse gas -induced global warming due to the land-sea thermal contrast [Intergovernmental Panel on Climate Change, 2001;Bueh, 2003;Bueh et al, 2003]. However, some recent studies based on instrumental measurements did not support the model projections.…”
Section: Discussionmentioning
confidence: 99%